Isolongifolene-Loaded Chitosan Nanoparticles Synthesis And Characterization For Cancer Treatment - Komaragunta, Kusuma; Varalakshmi, Mavallur (Journal of Neonatal Surgery, 2025)
The advancements of nanoparticle-based treatment approaches have revolutionized the cancer treatment strategy, as novel approaches have been adopted with success in the management of this disease in extending the time to the onset of the disease. Compared to other therapeutic leads used in conventional drug delivery nanoparticulate systems exhibit excellent penetrating power based on several factors and are most affecting in disease control. In the current study, isolongifolene ‑ loaded Chitosan nanoparticles have been formulated, synthesized and then characterized using Fourier transform infrared spectroscopy, X ‑ray Diffraction, Scanning Electron Microscopy, and Transmission Electron Microscopy. In addition, the characterized chitosan nanoformulation was tested in terms of bleeding time, plasma degradation, and also followed in simulated gastrointestinal media. Chitosan nanoparticles containing isolongifolene were shown to be stable in plasma and sustained the release profile. Therefore, chitosan loaded nanoparticles could be a suitable companion in cancer therapy to overcome multiple drug resistance of solid tumors.